1996
DOI: 10.1200/jco.1996.14.6.1818
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant therapy of high-risk gastric cancer: a phase II trial of preoperative FAMTX and postoperative intraperitoneal fluorouracil-cisplatin plus intravenous fluorouracil.

Abstract: Chemotherapy with the FAMTX regimen is tolerable in patients with locally advanced gastric cancer, without an increase in operative morbidity or mortality. IP therapy can be successfully delivered to most resected patients. The intraabdominal failure pattern appears to be decreased compared with expected. This approach is an appropriate investigational arm to pursue in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0
5

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(48 citation statements)
references
References 28 publications
3
40
0
5
Order By: Relevance
“…Interesting results have been initially reported with the use of the FAMTX regimen (5-FU, doxorubicin and methotrexate). In patients with high risk, but potentially curable, gastric tumours, 34 of 56 patients (61%) received a curative resection, but at the cost of substantial toxicity (mainly neutropenic fever) with one chemotherapy-related death (Kelsen et al, 1996). Nevertheless, data from a small randomised trial that compared the use of FAMTX as preoperative therapy before surgery vs surgery alone in operable gastric cancer could not demonstrate that the FAMTX regimen was suitable as neoadjuvant chemotherapy, and the authors concluded that more active regimens should be tested in further randomised studies (Songun et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interesting results have been initially reported with the use of the FAMTX regimen (5-FU, doxorubicin and methotrexate). In patients with high risk, but potentially curable, gastric tumours, 34 of 56 patients (61%) received a curative resection, but at the cost of substantial toxicity (mainly neutropenic fever) with one chemotherapy-related death (Kelsen et al, 1996). Nevertheless, data from a small randomised trial that compared the use of FAMTX as preoperative therapy before surgery vs surgery alone in operable gastric cancer could not demonstrate that the FAMTX regimen was suitable as neoadjuvant chemotherapy, and the authors concluded that more active regimens should be tested in further randomised studies (Songun et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly promising seemed data with regard to the use of EUS in preoperative staging of stomach tumours (Lightdale et al, 1989;Botet et al, 1991). Endoscopy and endoscopic ultrasonography showed an accuracy of 75 -85% in predicting tumour stage before surgery, but its use in the evaluation of response to treatment in patients, who received preoperative chemotherapy, was disappointing and unreliable probably due to chemotherapy-induced changes in the physical pattern of the tumour (Kelsen et al, 1996;Ajani et al, 1999). Nevertheless, before a more widely diffusion of these methods occur, traditional procedures are to be applied in order to define surgical resectability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment regimens and results are detailed in Table 4. In two studies, intraperitoneal chemotherapy was added postoperatively to eligible patients (4,67,74). Inclusion criteria were not uniform and the preoperative staging used many different imaging techniques.…”
Section: Preoperative Chemotherapymentioning
confidence: 99%